Israeli National Policy for Carbapenem-Resistant Enterobacteriaceae Screening, Carrier Isolation and Discontinuation of Isolation. (15th December 2017) - Solter, Ester; Adler, Amos; Rubinovitch, Bina; Temkin, Elizabeth; Schwartz, David; Ben-David, Debby; Masarwa, Samira; Carmeli, Yehuda; Schwaber, Mitchell J.
Abstract : Abstract: Since 2006, Israel has been confronting an outbreak of carbapenem-resistant Enterobacteriaceae (CRE), and in 2007 Israel implemented a national strategy to contain spread. The intervention was initially directed toward acute-care hospitals and later expanded to include an established reservoir of carriage in long-term-care hospitals. It included regular reporting of CRE cases to a central registry and daily oversight of management of the outbreak at the institutional level. Microbiological methodologies were standardized in clinical laboratories nationwide. Uniform requirements for carrier screening and isolation were established, and a protocol for discontinuation of carrier status was formulated. In response to the evolving epidemiology of CRE in Israel and the continued need for uniform guidelines for carrier detection and isolation, the Ministry of Health in 2016 issued a regulatory circular updating the requirements for CRE screening, laboratory diagnosis, molecular characterization, and carrier isolation, as well as reporting and discontinuation of isolation in healthcare institutions nationwide. The principal elements of the circular are contained herein. Infect Control Hosp Epidemiol 2018;39:85–89